Common variants in ZMIZ1 and near NGF confer risk for primary dysmenorrhoea - Zhiqiang Li (Nature Portfolio, 2017)
Primary dysmenorrhoea, the most common gynaecologic complaint, remains genetically and pathophysiologically elusive. Here, Li and colleagues identify common variants inZMIZ1 and near NGFconferring risk for primary dysmenorrhoea using genome-wide association study in a Chinese population.